Metabolomics-Based Clinical Efficacy of Compound Shenlu Granule, a Chinese Patent Medicine, in the Supportive Management of Aplastic Anemia Patients: A Randomized Controlled Pilot Trial. (30th September 2021) - Feng, Zhou; Hu, Xiaoying; Qu, Weiying; Zhu, Xiaoqin; Lu, Jiaying; Huang, Zhongdi; Zhao, Lin; Chen, Pei
Abstract : Objective . To explore the clinical efficacy and mechanism of compound Shenlu granule (SLG) treatment in patients with aplastic anemia (AA). Methods . A total of 89 AA patients were randomly divided into an SLG supportive group (group A, n = 44) and a control group (group B, n = 45) while continuing Western medical management. After 6 months, hemograms, traditional Chinese medicine (TCM) syndrome scores, and overall clinical efficacy rate were assessed. Serum metabolomics characteristics were observed using ultraperformance liquid chromatography-mass spectrometry after SLG intervention. Results . The levels of red blood cell (RBC), hemoglobin (Hb), and platelet (PLT) were increased in both groups after treatment for 6 months (P < 0.05 ), and in group A, the elevation of PLT became much more significant (P < 0.01 ). The TCM syndrome score was lower in group A than in group B after treatment (P < 0.05 ). Metabolomics data showed a significant difference in the patients using SLG after 6 months, and 14 biomarkers were identified. Conclusion . SLG supportive treatment showed positive results in patients with AA, and metabolomics data indicated that SLG influenced aminoacyl-tRNA biosynthesis and glycerophospholipid metabolism to gradually return to normal.